Adapting the Index of Relative Rurality (IRR) to Estimate Rurality at the ZIP Code Level: A Rural Classification System in Health Services Research. Issue 2 (23rd September 2015) - Inagami, Sanae; Gao, Shasha; Karimi, Hassan; Shendge, Martine M.; Probst, Janice C.; Stone, Roslyn A.
Abstract: Background: Accurate analysis of health problems facing rural residents depends on how rurality is defined. Health services research relies frequently on the rural urban commuting area (RUCA) codes to estimate rurality at the small area level. We modified the county‐level Index of Relative Rurality (IRR) to the ZIP code level (IRRZIP ) to create an alternative small‐area‐level rural classification system. We then compared how the 2 rural classification systems differ in how rural areas and populations are defined and in methodological analysis. Methods: We linked data for veterans (n = 37, 466) who attended the VA Pittsburgh Healthcare System to 2000 United States Census and the US Department of Agriculture's Economic Research Service data. Results: The RUCA and the IRRZIP do not consistently classify the same ZIP code areas and populations as rural. Using the IRRZIP, each 10th increment in increased rurality was associated with a 2.6 increased odds of receiving primary care at a satellite clinic. Conclusions: The IRRZIP is a straightforward measure that is easy to use and interpret and may be a relevant alternative rural classification system that can be used in health services research.